2020
DOI: 10.1002/qj.3798
|View full text |Cite
|
Sign up to set email alerts
|

Towards an unbiased stratospheric analysis

Abstract: The standard, strong‐constraint formulation of 4D‐Var is designed to correct for random, zero‐mean errors from the model forecast and the observations. However, significant systematic errors are generated by the forecast models used in global numerical weather prediction (NWP), and the Integrated Forecast System (IFS) model of the European Centre for Medium‐Range Weather Forecasts (ECMWF) is no exception. To deal with this type of error, a modification of the standard 4D‐Var algorithm, weak‐constraint 4D‐Var, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(68 citation statements)
references
References 36 publications
4
64
0
Order By: Relevance
“…These results confirm that estimating model error in the IFS at the rather coarse scales we are considering here is a mildly nonlinear problem, which can partly explain the success of WC-4DVar in its current configuration (Laloyaux, Bonavita, Chrust, et al, 2020;Laloyaux, Bonavita, Dahoui, et al, 2020). In the current WC-4DVar configuration only mass and (to a lesser extent) wind model errors are estimated and corrected, which also seems a good choice based on the results in Figure 2.…”
Section: Training the Annsupporting
confidence: 80%
See 4 more Smart Citations
“…These results confirm that estimating model error in the IFS at the rather coarse scales we are considering here is a mildly nonlinear problem, which can partly explain the success of WC-4DVar in its current configuration (Laloyaux, Bonavita, Chrust, et al, 2020;Laloyaux, Bonavita, Dahoui, et al, 2020). In the current WC-4DVar configuration only mass and (to a lesser extent) wind model errors are estimated and corrected, which also seems a good choice based on the results in Figure 2.…”
Section: Training the Annsupporting
confidence: 80%
“…This is also in view of the complex and typically nonlinear model error interactions that arise between the various components of a coupled Earth system model during extended integrations. We note, however, that recent results in both medium range NWP (Laloyaux, Bonavita, Dahoui, et al, 2020) and seasonal prediction (Ham et al, 2019) have already shown that the introduction of pure or hybrid ML/DL models can lead to significant improvements in specific aspects of forecast performance.…”
Section: Research Perspectivesmentioning
confidence: 73%
See 3 more Smart Citations